Análise energética de vedantes de rolamentos de esferas para diferentes graxas lubrificantes e condições de operação - Daniliszyn, Dennis Leonardo (2019)
This present conclusion course paper was developed in the laboratories of the Federal Technological University of Paraná, Curitiba campus, being of numerical-experimental character . Bearings are mechanical components with the purpose of transmitting movement and/or forces. Its application, however, is always associated with frictional energy losses that directly impact the useful life of these components and consequently can generate large economic losses due to frequent replacement need. A portion of the friction in bearings is the result of the coupled seals. Considering these facts, this work studied the influence of different types of greases through a comparison between two different models of friction presented in the literature. Thus, new studies can be with the purpose of generating solutions to attenuate the energy losses caused by friction in the seals.